If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-6x + 2) = -1(6x + -174) Reorder the terms: 3(2 + -6x) = -1(6x + -174) (2 * 3 + -6x * 3) = -1(6x + -174) (6 + -18x) = -1(6x + -174) Reorder the terms: 6 + -18x = -1(-174 + 6x) 6 + -18x = (-174 * -1 + 6x * -1) 6 + -18x = (174 + -6x) Solving 6 + -18x = 174 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 6 + -18x + 6x = 174 + -6x + 6x Combine like terms: -18x + 6x = -12x 6 + -12x = 174 + -6x + 6x Combine like terms: -6x + 6x = 0 6 + -12x = 174 + 0 6 + -12x = 174 Add '-6' to each side of the equation. 6 + -6 + -12x = 174 + -6 Combine like terms: 6 + -6 = 0 0 + -12x = 174 + -6 -12x = 174 + -6 Combine like terms: 174 + -6 = 168 -12x = 168 Divide each side by '-12'. x = -14 Simplifying x = -14
| senx=-1/2 | | X+1=7+4x | | 435-31x=179 | | v/4-14=3 | | 5-4cos^2x=4sinx | | 43=3u-17 | | 3x^2+9=x^2+27x | | 8.1x-4.1=12.1 | | 4sin^4x-13sin^2x+3=0 | | 4w+11=59 | | eqnforh=3k=4 | | -2w+7=w+2.5 | | -16x-15=-63 | | 2n^2-12=5n | | 4h+k=16h+2k=11igotansash=3k=4 | | Y=(7)4-3 | | 3r^2-12r=15 | | -3+8y+3=-24x | | 1+4r+1=14 | | 3+4+4*x= | | 10=-2r-3r | | y=1/x^2-7 | | 5-(2x+1)=-2 | | 4h+k=16h+2k=11 | | 13.2+n=15 | | -40=12times+8 | | 7x-(4x+1)=-79 | | 7x^2=-60x-32 | | 4=m+4+4m | | 15y+2x+2=14 | | 5(n+6)+20=10 | | 5x-66=3x-14 |